Frontal recess anatomy and its association with the development of frontal sinusitis : computed tomography study - Johari, Hafizah Husna (2018)
Objective: This study was done to determine frontal recess anatomy cell variations and its association with frontal sinusitis. The incidence of frontal recess cells in the population, the presence of frontal recess cell variations in chronic rhinosinusitis and non-chronic rhinosinusitis and the association of frontal recess cell variation in the development of frontal sinusitis were also assessed. Methodology: This was an observational, retrospective cross-sectional study of computed tomography paranasal sinus that had been performed on patients in Hospital Universiti Sains Malaysia and Hospital Sultanah Bahiyah done from January 2009 until December 2016. Results: A total of 312 sides from 156 patients’ CT scan images were analyzed. Left and right sinuses were considered individually. A total of 63 sides showed evidence of frontal sinusitis, 37 were male and 26 were female, whereas 249 sides were clear from frontal sinus disease. It was not much difference in mean age for frontal sinusitis patient (46.51±14.00) and patients without frontal sinusitis (48.73±16.44). The percentage were almost equal for CRS and non-CRS groups regardeless of side and gender. In our study, the frontal recess cell such as agger nasi cell was found in almost all patients 98.1%, frontal ethmoidal cell type 1, type 2, type 3 and type 4 comprised of 28.8%, 31.1%, 14.4% and 0% respectively. Whereas, suprabullar cell can be seenin 40.3%, supraorbital ethmoid cells 16.7%, frontal bullar cell 33.0% and inter-frontal sinus septal cells 10.8%. The presence of frontal recess cells variation was compared with other populations. There was a statistically significant association between the presence of frontal bullar cell and the development of frontal sinusitis (p value < 0.001). Conclusion: The frontal recess cells variation in Malaysian subjects were almost similar to those reported in other Asian populations such as Japanese, Taiwanese, Chinese and Korean. Our study found that frontal bullar cells had a significant association with the development of frontal sinusitis than other frontal recess cells. The understanding of the frontal recess anatomical structures was very important as this would lead to a successful treatment of CRS and at the same time it helped the surgeon to have a better plan of endoscopic sinus surgery to prevent the disease recurrence and surgical complication.